Effectiveness and Limitations of Monetary Policy Instruments in Romania and the European Union - Zina Cioran (CES Working Papers, 2014)
The complexity of the monetary phenomenon as well as the effects that it induces in the social and economic life of the countries around the world have represented and still represent the subject of much controversy and dispute. The current forms of the monetary circulation organization in different countries, internationally as well, represent the result of a continuous process of changes and innovations in the monetary area. The purpose of this article is to present aspects of the monetary policy and its instruments which have evolved according to the historical conditions of each period. The paper is also a presentation of effectiveness and limits of the monetary policy instruments and their role in solving the current economic problems for which the governments seek solutions. As a consequence to the analysis, it can be seen that in most cases it uses a mixture of monetary policy instruments because, when acting in a complementary way, they have a higher efficiency.
Keywords: E31; E43; E52; E58; 330; monetary policy; inflation; Central Banks; monetary policy instruments; money supply